Herbal Remedies : Dozens of safe, effective treatments to grow and make - Fisher, Katheen (Emmaus Pennsylvania : Rodale Press, Inc., 1999)
herbs,--Herbal healing formulas.--Essential healing herbal,--Essential healing herbs A to Z.--Growing healing herbs.--Symptoms and remedies.--Herbal resources.
Incluye Index
Keywords: Hierbas medicinales y aromáticas